Hesitant to pull the trigger: how the perceived impact of guns on campus influences support or opposition to campus carry laws - Scherer, Heidi L. (Journal of crime and justice, 2021)
A growing body of research has examined the factors that determine support for campus carry among campus populations, however, most have only focused on how demographic characteristics, campus safety measures, and gun ownership and attitudes impact support for campus carry. Another important, yet unstudied factor relates to how campus members think having guns on campus will impact their campus life activities. This study fills this gap in past research by exploring how the perceived academic- and employment-related impacts of campus carry influence support for the law. Stepwise multivariate logistic regression models were estimated by campus population using a sample of faculty, staff, and students from a large public university in Georgia (N = 2,545). Academic- and employment-related perceived impacts had a significant impact on support for the campus carry law across each of the campus groups even after controlling for empirically supported and relevant theoretical predictors such as campus safety concerns and gun attitudes and exposure. This study illustrates the need to include perceived impacts of the law in future research on campus carry and sheds light on the implications of campus carry on the routine activities of campus members.